Silver-bacterial cellulosic sponges as active SERS substrates - Marques, Paula A. A. P. (2008)
Synthetic Ag-bacterial cellulose nanocomposites are reported here and their performance as surface enhanced Raman scattering (SERS) substrates was investigated using thiosalicylic acid and 2,2 - dithiodipyridine as analytes. These nanocomposite materials act as natural sponges when immersed in aqueous or ethanolic solutions allowing capture and SERS detection of certain dissolved molecules. The detection limits for the above organic analytes reached concentrations as low as 10−4 mol·dm−3 and are considerably lower than the conventional vegetable cellulose analogs. Furthermore, we anticipate that the use of these nanocomposites has a beneficial consequence for the development of handy and active cellulosic SERS substrates, in particular for bioanalysis, as we experimentally demonstrated by testing the amino acids L-phenylalanine, L-glutamin and L-histidine.